Blood flow in non-muscle tissues and organs during exercise: Nature of splanchnic and ocular circulation - Naoyuki Hayashi; Masako Yamaoka-Endo; Nami Someya; Yoshiyuki Fukuba (Japanese Society of Physical Fitness and Sports Medicine, 2012)
In response to increased vascular conductance associated with vasodilation in exercising muscles, many non-exercising organs suppress their blood flow by vasoconstriction, thus helping to maintain blood pressure. This vasoconstriction in non-exercising organs contributes to ensuring a favorable distribution of the blood flow. However, a consequent excessive decrease of blood flow in non-exercising organs should be avoided so that they can maintain appropriate functioning during and/or after exercise. There is now evidence of a decrease in splanchnic blood flow with vasoconstriction during dynamic exercise, which indirectly contributes to an increase in flow in exercising muscles. Hypoperfusion in the splanchnic area, induced by such vasoconstriction, may result in gastrointestinal symptoms. On the other hand, such vasoconstriction is suppressed when exercise is performed after food intake, which may be associated with the maintenance of digestive and absorptive functions in the gastrointestinal tract. In contrast to organs that decrease their blood flow, the choroidal flow, which forms part of the ocular blood flow, increases with exercise intensity, but without vasodilation. The relevance of this phenomenon to visual function and the nature of ocular circulation remain unclear. Competition in blood flow between exercising muscles and non-exercising organs should be examined from the viewpoint of the functions of non-exercising organs and exercising condition, such as the postprandial condition.